Elaboración de un manual de seguridad industrial para la aplicación en el taller industrial “Hornos Lincoln”, en la parroquia Maldonado de la ciudad de Riobamba durante el año 2016. - Manobanda Andagana, Cristian Iván (2016)
The following study seeks to contribute to the prevention of industrial accídents at the Líncoln Furnaces Industry in the city of Riobamba, with the development and application ofthe Industrial Safety Manual (MSI). In addition to knowing the conditions of occupational hazards faced by employees, they also identifiedthe 1evelsof safety that are applied in the production processes that are carried out in the workshop. For this, a field research oftype and descriptive level was carried out with the purpose of knowing the needs and problems that arise during the development of the industrial activities, an interview was maintaíned with the owner, a survey was carried out to the18 employees who Elaborated in the company and used other instruments like notes, checklist and camera; As a result of this study it is known that approximately 90% of workers are unaware or have implemented industrial safety standards for having had two or more occupational accidents; In relation to the work environment, 67% of the staff stated that there are still areas that are susceptible to accidents in the workshop and are not attended due to lack of coordination, apathy or lack ofleadership. Respect to the applied securitylevels; No signs of safety or evacuationroutes are evident. Before this, an industrial safety manual is implemented as a practical too1to know and execute preventive measures in the workshop; Will serve to prevent, reduce and eliminate work accidents, also to maintain a culture of responsibility with health and generate greater business competitiveness, the material is developed with methodological guidelines so that users achieve meaningfu1leaming.